A two-step nonthermal plasma method to fabricate Ag/N- doped TiO2/CNTs for formaldehyde removal under visible light irradiation. (10th October 2022) - Tan, Yujie; Sun, Luying; Wang, Guicheng; Zhang, Ruina; Hou, Jianyuan; Zhang, Renxi; Zhao, Weixuan
Abstract: A novel efficient catalyst called Ag/N-doped TiO2 /CNTs was fabricated using a two-step method involving treatment with ammonia plasma followed by a process of hydrogen plasma reduction at a low temperature. The photocatalyst, which was composed of silver nanoparticles (AgNPs), titanium dioxide (TiO2 ) and 5% amount of carbon nanotubes (CNTs), achieved an adequate formaldehyde elimination rate of 95% under visible-light irradiation. A series of analytical methods was employed to investigate the advantages of the novel fabrication method. The results showed that the first step, which is the N doping of TiO2 could be particularly important for improving the photocatalytic performance because of the reduced band gap and newly formed Ti 3+ . Furthermore, it could assist in the anchor of AgNPs during the second step of fabrication. During the second step of hydrogen reduction process, AgNPs of smaller sizes were more homogeneously anchored on the surface of N-doped TiO2 /CNTs than that of the catalysts without ammonia plasma treatment. The resulting higher level of AgNPs could aid in efficient electron transfer and significantly improve the response to visible light, considering the surface plasmon resonance effect. CNTs and AgNPs played significant roles as electron acceptors in reducing the recombination rate of photogenerated hole pairs, and moreover, this two-step plasma process could be beneficial for achieving surface and interface properties suitable for formaldehyde photodegradation. This novel approach for fabricating an efficient Ag/N-doped TiO2 /CNTs has potential for application in environmental purification systems. Graphical abstract: Image 1 Highlights: A novel two-step nonthermal plasma method can be used for photocatalyst fabrication. Nitrogen atoms doping could help with Ag nanoparticles to anchor. Plasma process and element doping have a synergistic effect to enhance the catalyst. The contribution of the CNTs and Ag nanoparticles were identified. The mechanism of Ag/N-doped TiO2 /CNTs for degradation of HCHO was discussed.